Incidence and risk factors of perineal tears of pregnant women delivering at a midwife obstetric unit South Africa - Hoque, Akm Monjurul; Buckus, Somaya (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aim: To estimate the incidence and risk factors for perineal tears of low-risk pregnant women delivering at a midwife obstetric unit.Methods:  A retrospective study performed on perineal tear during childbirth from birth register at midwife run unit in Durban municipality, South Africa between January 2018 and October 2019. Risk factors were studied and bivariate and logistic regression done. Results are expressed with adjusted odds ratios (OR) and p-values